2009
DOI: 10.1007/s11095-009-9868-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in Frozen Systems and During Freeze–Drying: Quantification Using Synchrotron X-Ray Diffractometry

Abstract: A high-intensity X-ray diffraction method was developed to monitor the phase transitions during the entire freeze-drying cycle. The high sensitivity of SXRD allowed us to monitor all the crystalline phases simultaneously. While DHPD crystallizes in frozen solution, it dehydrates incompletely during primary drying and completely during secondary drying. The impact of initial solute concentration on the phase composition during the entire freeze-drying cycle was quantified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Studies have shown that the crystallization of sodium phosphate buffer can be inhibited in the frozen state by the incorporation of glycine at a low ratio [52]. However, if the molar ratio of glycine to sodium phosphate is too high, this can lead to the crystallization of glycine.…”
Section: Phosphate Buffermentioning
confidence: 99%
“…Studies have shown that the crystallization of sodium phosphate buffer can be inhibited in the frozen state by the incorporation of glycine at a low ratio [52]. However, if the molar ratio of glycine to sodium phosphate is too high, this can lead to the crystallization of glycine.…”
Section: Phosphate Buffermentioning
confidence: 99%
“…173 The lyophilization process presents another opportunity for phase transitions to take place during the processing of drug products, and in one study, aqueous sodium phosphate solutions (buffered with glycine) were used as a model system to investigate the effect of initial solute concentration on the crystallization of glycine and phosphate buffer salt during lyophilization. 174 In another study, the polymorphic identity of mannitol lyophilized from an ethanol-containing solution was studied as a function of the ethanol ratio, mannitol concentration, and annealing conditions used in the freeze-drying cycle. 175 The effect of concentration of two Fc-fusion proteins on the crystallinity and polymorphism of mannitol and sodium chloride in a lyophilized model formulation has been examined.…”
Section: Effects Associated With Secondary Processing Of Crystal Formsmentioning
confidence: 99%
“…These excipients are incorporated to exert specific functions, wherein their desired physical form, both during processing and in the final product, can potentially influence the product stability and hence the performance (3)(4)(5)(6). Crystallization of bulking agents is desirable, both from processing and productelegance perspectives (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Lyoprotectant crystallization reduces its effectiveness (16,17). The physical state of an excipient not only determines its own functionality, but can also influence the solid state of other solutes including the API (6). For example, crystallization of glycine enhanced the crystallization of sodium phosphate buffer in frozen solutions.…”
Section: Introductionmentioning
confidence: 99%